Pedagogical Conditions for the Development of Individual Characteristics of Students of a Higher Educational Institution - Jamalova Nafisa O'tkirovna (International Journal on Integrated Education, 2022)
this article deals with the pedagogical conditions for the development of individual characteristics of students in higher establishments. In addition, author provides several propositions of prominent researchers who contributed in the sphere of pedagogy and psychology.